Best Answer

Multiply first equation by 3: 9x + 15y = 63

Add that and second equation: 19y = 57

Divide by 19: y = 3, so x = 2

Study guides

☆☆

Q: 3x plus 5y equals 21 -9x plus 4y equals -6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(2, -1)

2x + 3y = 17 3x + 4y = 24 (2x + 3x) + (3y + 4y) = (17 + 24) 5x + 7y = 41

x = 4 and y = 0

(-1, 5)

(1, 1)

Related questions

(2, -1)

x = 2, y = 3

2x + 3y = 17 3x + 4y = 24 (2x + 3x) + (3y + 4y) = (17 + 24) 5x + 7y = 41

4y = 3x+11 or as y = 3/4x+11/4

x = 4 and y = 0

(-1, 5)

(-1, 5)

(1, 1)

It is:- 3x+4y = 8 4y = -3x+8 y = -0.75x+2 So the slope is -0.75 and the y intercept is 2

It is: 3x+4y which is an algebraic expression

Yes.

3x=4y-x 4x=4y x=y